Effect of isolated and combined core strength training and yoga practices on selected biomotor variables among adolescent school boys (International Journal of Food and Nutritional Sciences, 2022)
The core described as the human body except for limbs, specifically as runners and yoga have a long history and a rich depth of knowledge and are both essential aspects to examine and investigate in people. Based on the concept the study design to find out the effect of isolated and combined core strength and yoga practices on selected biomotor parameters of adolescence boys. For the purpose of the study 45 Adolescent School boys from Government Higher Secondary School Kumarachi, Tamil Nadu were selected as subjects. The age rang of the selected subjects from 14 years to 17 years. The subjects were divided into three groups of fifteen namely core strength training group (n=15), yoga practice group (n=15) and combined core strength yoga practices group (n=15). The speed and explosive power were selected as biomotor variables. The variables were tested by using 50 m dash and Sarjent jump. The experimental groups underwent there training for 12 weeks, 4 days per week, 45 to 60 minutes per day with suitable warming up and cooling down exercise. The criterion variables were tested prior to and immediately after the training programme. The collected data were analysed using ANCOVA (analysis of covariance) and scheffe’s post hoc test was applied to know the paired mean differences if the optioned ‘f’ ratio was significant. The level of significance fixed at.05. After investigating the study, there was a significant difference among experimental groups on selected speed and power parameters. The study also shows that the combined training group shows better improvement on criterion variables when compared with isolated training groups.